Genetic diversity among 24 clones of robusta coffee in Lampung based on RAPD markers - Sri Ramadiana; Dwi Hapsoro; Rusdi Evizal; Kukuh Setiawan; Agus Karyanto; Yusnita Yusnita (Society for Indonesian Biodiversity, 2021)
Abstract. Ramadiana S, Hapsoro D, Evizal R, Setiawan K, Karyanto A, Yusnita. 2021. Genetic diversity among 24 clones of robusta coffee in Lampung based on RAPD markers. Biodiversitas 22: 3122-3129. This study aimed to estimate the genetic diversity among 24 clones of Robusta coffee from Lampung, Indonesia, by use of RAPD markers. The clones consisted of 18 local and 6 BP clones. These BP clones were developed from a breeding program of The Indonesian Coffee and Cocoa Research Institute. Genomic DNAs extracted from these clones were subjected to polymerase chain reaction and the amplified products were run using gel electrophoresis. Eleven random primers produced clear, reproducible, scorable bands. Fifty-four of 86 bands showed polymorphism and were used to construct a dendrogram based on UPGMA Jaccard's Similarity Coefficients. The genetic base of the population was narrow (average genetic similarity 68.4%), ranging from 26-93%. The genetic similarity of the local clones was higher than that of BP clones. The clones were clustered into five groups. Group 1 contained one clone (BP 534), while each of Group II-V contained more than one clone. The average genetic similarity of BP 534 to each clone of Group II-V was 41%. The genetic similarity of clones in Group II, III, IV, and V were 55.5%, 43.0%, 81.1%, and 80.1%, respectively. This research should be very useful for selecting parents in a breeding program to produce better clones of Robusta coffee.